Effect of Peer Education on Self Care Patients Diabetes Mellitus in RSUD Panembahan Senopati Bantul Yogyakarta - Dewi Wijayanti; Untung Sujianto; Achmad Zulfa Juniarto (Alma Ata University Press, 2018)
Self Care is an implementation of activities based on self-awareness and conducted by the individual itself to meet the needs in maintaining life, health, and well-being in accordance with the state of health and illness.Employment of independence conducted by patients Diabetes Mellitus (DM) called self care DM with one of the goals in performing independent actions is to control the Diabetes Mellitus so as to minimize the occurrence of complications.Edukasi is a source of information that can help diabetes mellitus patients in taking decisions appropriate self-care nursing actions.The purpose of this study is to determine the influence of peer education against self care in patients with Diabetes Mellitus. Type of quantitative research with quasi experimental research design pre-test and post-test control group. The number of samples in this study were 21 patients with Diabetes Mellitus in the Hospital according to inclusion criteria and exclusion in the study. Sampling using purposive sampling technique, data collection using questionnaire The Personal Models Of Self Care Diabetes Questionnaire that consists of 9 items of questions. The research analysis used univariate and frequency distribution. The results showed that patients with Diabetes Mellitus self care category as much as 16, 7% and self care with less good category as much as 83, 3 %. Based on the results of the study, it can be concluded that self care nursing diabetes mellitus patients in performing self actions to minimize the occurrence of complications in the category less good.